Gender-based violence among healthcare students: Prevalence, description and associated factors. - Marie-Pierre Tavolacci; Alice Karmaly; Najla El Gharbi-Hamza; Benoit Veber; Joel Ladner (PLoS ONE, 2023)
Objectives The aims of the current study were 1) to provide the prevalence of five types of gender-based violence (GBV) among male and female healthcare students; 2) to describe perpetrators' status, where the GBV occurred, and psychological and behavioural impacts of the GBV; and 3) to identify factors associated with GBV. Design A cross-sectional study was conducted among voluntary healthcare students in France. Setting Health Campus at Rouen and nursing schools in Normandy, France. Participants Volunteer healthcare students of 18 years and over. Data collected Five types of GBV were recorded: GBV1: damage to a person's image due to a sexual connotation on social networks, GBV2: sexist remarks and behaviour, GBV3: comments with sexual connotations, GBV4: sexual assaults and GBV5: rape or attempted rape. Perpetrators' status, where the GBV occurred, psychological and behavioural impacts of GBV were also recorded. Results One thousand one hundred and fifty-two students were included. The mean age was 20.8 years (SD = 2.26), 82.6% of students were women (0.4% non-binary). Since the beginning of their healthcare study, 41.2% of students CI 95% [39.7-42.6] were victim of at least one type of GBV: 15.8% among men CI 95% [13.2-18.4] and 46.0% CI 95% [44.4-47.6] among women (p < 0.001). The perpetrators were student peers, regardless of the type of GBV, healthcare workers for the GB2 and GBV3, and patients except for GBV5. The main consequences of GBV on health was psychological and eating related. After multivariate analysis, being a woman, LGBTQ+ (Lesbian, Gay, Bi, Trans, Queer and other), a nurse, a physiotherapist student, having a job, living with roommates and year of study were risk factors for GBV. Conclusion GBV is so common at healthcare universities and could have such severe consequences for students that more work is needed to generate a culture change and ensure safe learning environments.